Artificial Intelligence for Managing Diabetes Mellitus in Indonesia Implementation Challenge in Resource-Limited Settings - Veramita Augusta Arisandy; Shafira Maharani Malik (PP PERKENI, 2024)
The existence of Artificial Intelligence (AI) has shaped a significant transformation in healthcare. In the field of endocrinology, AI has been used in the treatment of diabetes mellitus which categorized as one of the leading causes of death in Indonesia. This study is based on a general article review that uncovered the function of AI and its utilization on diabetic care. Currently, AI has grown into a facility that plays a role in health care, such as screening, diagnosis, and recognizing problems. In the scope of diabetes, several AI-based methods and applications have been investigated and played a role in diabetes management such as monitoring blood sugar, setting therapy targets, and dietary adjustment in diabetic patients. Despite the sophistication of AI, there are still several potential risks and barriers, notably in Indonesia, where the limited resources still be an impediment to the use of advanced technology. Lack of data integration and limited accessibility are the common challenges to AI implementation in limited-resources areas. Nevertheless, the application of AI offers numerous prospective benefits, particularly in terms of convenience of use and its efficacy in diabetes management to optimize diabetes care with standardized digital data records, resource improvement, and workload decrease.